The Influence of Macroeconomic Factors and Financial Performance on Dividend Policy During Pandemic (Manufacturing Company Listed on the IDX) - Rinanda, Yessi (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This study aims to analyze the influence of macroeconomic factors and financial performance on dividend policy during the pandemic in manufacturing companies listed on the IDX. Shareholders have an interest in obtaining periodic returns on their investments in the form of dividends distributed by the company. The variables used in this macroeconomic factor are inflation, interest rates, and the rupiah exchange rate h. In order to be able to distribute dividends, companies must also have healthy financial performance. The influence of financial performance as reflected in financial ratios in terms of profitability, capital and liquidity which in this case is reflected in the ratio of Return on Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER ), Earning Per Share (EPS) . The population in this study are all manufacturing sector companies listed on the Indonesia Stock Exchange. This research uses multiple regression analysis processed with EVIEWs . The results of this study indicate that the macroeconomic factors in the form of the inflation rate and the interest rate have no significant effect on the dividend policy of manufacturing companies on the Indonesia Stock Exchange. Financial performance factors show that ROA, ROE, and EPS have a significant effect on dividend policy for manufacturing companies on the Indonesia Stock Exchange.